(untitled) (Desarrollo, Estado y Espacio, 2024)
China’s energy transition strategy is having consequences for countries in the Global South. Being rich in critical minerals, countries in Latin America have emerged as significant suppliers for China and important destinations for Chinese companies’ investments. These engagements have coincided with increasing global competition between Chinese and other leading companies to access and control these key transition materials, placing countries in the region as an arena of contending ambitions. Argentina is a good example of these trends. This paper analyzes Chinese companies’ investments in the Argentine lithium sector, focusing on the implications for Argentina’s economic development and international insertion. Based on the contributions of Latin American structuralism, but also new approaches that recover the centrality of the State for promoting the industrialization process, the paper discusses the challenges peripheral countries such as Argentina encounter to achieve development within the global structure of center-periphery relations. To do so, we build a case study based on original data. The analysis first identifies the distinctive characteristics of Chinese firms operating in Argentina, distinguishing their interests and strategies. Subsequently, we address the domestic and global factors that limit Argentina’s possibilities for advancing toward more value-added activities locally. In the conclusions, we sum up the challenges Argentina faces regarding the industrialization of lithium and the role that Chinese and other foreign firms can play in contributing to building those capacities.